2013
DOI: 10.1113/jphysiol.2012.241125
|View full text |Cite
|
Sign up to set email alerts
|

Early postinjury exercise reverses memory deficits and retards the progression of closed‐head injury in mice

Abstract: Key points• Exercise benefits the brain in many ways, e.g. promoting neuron repair and inhibiting neuroinflammation. However, current clinical practices often advise patients suffering head injury to rest during the post-traumatic period.• This study used a mouse model to investigate whether and how exercise retarded the brain structural and functional losses induced by a head impact.• An early moderate-exercise protocol (starting 2 days postimpact and lasting for 7 or 14 days) reversed the impact-induced rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Additionally, both diet and exercise has been proven to be an effective remediation technique following TBI (Griesbach et al, 2009; Wu et al, 2011; Ying et al, 2012; Tyagi et al, 2013). Increased exercise in rodents within 2 days after injury improved cognitive deficits associated with object recognition memory (Chen et al, 2012) while an exercise regimen 3 months after injury improved working memory (Piao et al, 2013). Similarly, environmental enrichment has also been shown to improve both recovery and cognition in male and female rats (Matter et al, 2011; Cheng et al, 2012; Monaco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both diet and exercise has been proven to be an effective remediation technique following TBI (Griesbach et al, 2009; Wu et al, 2011; Ying et al, 2012; Tyagi et al, 2013). Increased exercise in rodents within 2 days after injury improved cognitive deficits associated with object recognition memory (Chen et al, 2012) while an exercise regimen 3 months after injury improved working memory (Piao et al, 2013). Similarly, environmental enrichment has also been shown to improve both recovery and cognition in male and female rats (Matter et al, 2011; Cheng et al, 2012; Monaco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, exercise seems to influence microglia through increased expression of CX3CL1, which confers on microglia the ability to up-regulate NPC proliferation. In other studies, exercise in animals was found to decrease age-related basal microglial proliferation (Kohman et al, 2012), and to lower microglial activation in models of hypoxia (Lin et al, 2012), high-fat diet (Yi et al, 2012), tau overexpression (Leem et al, 2011), and closed-head injury (Chen et al, 2012), further supporting the notion that exercise can play a role in deactivating and de-priming microglia. The molecular mechanisms underlying how exercise mediates these effects will be a fascinating area for future study, and may discover agents that can elicit exercise-induced effects without the need for actual exercise.…”
Section: Can Microglia Be Rejuvenated?mentioning
confidence: 92%
“…Treadmill exercise also improves hippocampus-dependent spatial learning and memory as well as aversive memory [2, 3, 25, 97, 112, 174, 186, 187]. Furthermore, in rodent models, BDNF, insulin– like growth factor 1 (IGF-1), mitogen-activated protein kinase phosphatase-1 (MKP-1), and glial-derived neurotrophic factor (GDNP) are elevated by exercise [1, 53, 179] and early post-injury exercise has been shown to reverse memory deficits and inhibit the progression of neurodegeneration following TBI [27]. …”
Section: The Benefits Of Exercise and Sports Participationmentioning
confidence: 99%